Benefit-Cost Analysis of Bioretention for Suburban Drainage Load Reduction Induced by Surface Runoff - Putri, Fidyasari Kusuma; Robbani, Hilma Wasilah; Pranantya, Vanadani; Widiarti, Wiwik Yunarni; Wiyono, Retno Utami Agung (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
Suburban areas with predominantly residential land use and low soil infiltration rates are highly vulnerable to surface runoff and local flooding. This study examines the effectiveness and economic performance of bioretention systems as a runoff management solution in the Wonojati and Jenggawah areas, Jember Regency. Hydrological simulations were conducted using SWMM 5.2 software for two intervention scenarios, namely the application of bioretention in 10% and 20% of the subcatchment areas. The effectiveness of the system was evaluated based on runoff volume reduction, while the economic aspect was assessed using the Benefit-Cost Ratio (BCR) approach. The simulation results showed that the system reduced runoff by 13.6% in Plan 1 and 17.4% in Plan 2. However, BCR values of 0.014 and 0.022, respectively, indicate that the annual financial benefits are not sufficient to cover the system’s annualized costs. These findings highlight the need for alternative approaches that are more economically efficient. The use of decentralized LID systems such as rain barrels is considered more adaptive for dense residential areas and is recommended as a complementary solution to enhance the resilience of drainage systems in flood-prone suburban regions.